A Feminist Critique of Patriarchy: Rokeya Sakhawat Hossain (1880-1932) - Ray, University of Calcutta, India, Bharati (Asiatic: IIUM Journal of English Language and Literature, 2013)
Rokeya Sakhawat Hossain was one of the most brilliant thinkers of colonial India in the twentieth century. She addressed women, primarily Muslim women, and censured them for their degraded condition in society and loss of self-respect. She ascribed women’s subjection to men to the patriarchal social structure that gave hegemony of men over women. She also blamed men for their selfishness and condemned the prevalent social and religious customs, formulated by men, which perpetuated women’s dependence. If women were in a position to frame them, these unfair customs would certainly have been different. Her call was to women to wake up, to acquire fruitful education instead of useless ornaments and go in for gainful employment that would establish equality with men. Extremely brave and radical seen in the backdrop of her time, she was a champion of gender equality and a precursor of the women’s movement in South Asia in the modern period.